A simple method for the isolation of lycopene from Lycopersicon esculentum - Kyun Roh, M.=700 1 Hee Jeon, M.; Nam Moon, J.; Sook Moon, W.; Mee Park, S.; Suk Choi, J.
(Es, En)
Ilus., 18 ref.
Keywords: LYCIOPERSICON ESCULENTUM; LICOPENO; CAROTENOIDES; PRECIPITACION QUIMICA; MEXICO